The effect of interventional pain management on treating postherpetic neuralgia - Suqian Guo; Mengxi Shen; Linlin Zhang; Qi Zhao; Chengcheng Song; Wei Jia; Guolin Wang (Wolters Kluwer Medknow Publications, 2019)
Background: Herpes zoster (HZ) is identified to induce postherpetic neuralgia (PHN) which is difficult to cure. PHN-related pain brings patients not only physical discomfort but also mental depression and anxiety. Currently, the main purpose of PHN treatment is to reduce patients' pain. Now treatment combining some international pain management and drug therapy has come up. Aims and Objective: This study aims to evaluate the effect of interventional management through meta-analysis. Materials and Methods: Interventional pain management was defined as a direct strategy on nerve through physical or chemical method. Drug therapy was always regarded as control. Potentially relevant articles were searched in PubMed, EMBASE, and the Cochrane Library through key words by consensus. Pain severity was evaluated by a validated visual analog scale (VAS). Moreover, the weighted mean difference was used to calculate pain intensity. Some trails recorded the efficiency rate and odds ratio was used to calculate the effectiveness. Statistical heterogeneity was measured by the value of I2, and when statistical I2 > 50%, subgroup analysis was used to seek for the source of heterogeneity. Results: Pulsed radiofrequency (PRF) combined with medication reduced the VAS scores at 1, 2, 4, and 8 weeks after treatment. The nerve block combined with medication reduced VAS scores at 8 weeks after treatment, but there is no difference between the results of medication alone at 1, 2, and 4 weeks after treatment. Conclusion: The interventional mean of PRF combined with medication has a good effect on PHN. The effect of nerve block combined with medication on PHN seems to be the same as that of medication alone. Besides, a long period with high-quality randomized controlled trial should be done to verify the results.